2021
DOI: 10.3390/molecules26164745
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics-Rich Extracts of Dietary Plants as Regulators of Fructose Uptake in Caco-2 Cells via GLUT5 Involvement

Abstract: The latest data link the chronic consumption of large amounts of fructose present in food with the generation of hypertension and disturbances in carbohydrate and lipid metabolism, which promote the development of obesity, non-alcoholic fatty liver disease, insulin resistance, and type 2 diabetes. This effect is possible after fructose is absorbed by the small intestine cells and, to a lesser extent, by hepatocytes. Fructose transport is dependent on proteins from the family of glucose transporters (GLUTs), am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…At this dose, ELE-treated cells did not show different morphological features, as confirmed by transepithelial/endothelial electrical resistance (TEER) and microscopic analyses; before and after fructose permeation, the TEER values of the blank and ELE (1 mg/mL) were retained by 91% and 81%, respectively. Many studies have reported various polyphenols derived from edible plants with inhibitory activity against fructose absorption [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. We examined the effects of the ELE with reduced polyphenolic substances.…”
Section: Resultsmentioning
confidence: 99%
“…At this dose, ELE-treated cells did not show different morphological features, as confirmed by transepithelial/endothelial electrical resistance (TEER) and microscopic analyses; before and after fructose permeation, the TEER values of the blank and ELE (1 mg/mL) were retained by 91% and 81%, respectively. Many studies have reported various polyphenols derived from edible plants with inhibitory activity against fructose absorption [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. We examined the effects of the ELE with reduced polyphenolic substances.…”
Section: Resultsmentioning
confidence: 99%
“…In-depth studies have shown that the MSNBA binding site is close to the active center of the GLUT5 protein and is responsible for substrate recognition by residue H387, as well as residues such as Ser143, Thr171, Gln288, Gln289, Asn294 and Tyr297 involved in the binding process of MSNBA-GLUT5 [95] . Recently, researchers have found that some phenolic-rich dietary plant extracts can reduce the transcript levels of the gene encoding ChREBP, thereby inhibiting GLUT5 protein expression and its mediated fructose transport [96] . This may contribute to our better understanding of the regulation of GLUT5 expression by plant compounds present in the human diet.…”
Section: Glut5 Inhibitormentioning
confidence: 99%
“…Table 2 summarizes the data available on the effect of PP-rich products on FRU uptake and transport in intestinal cells. Gallic acid (8.1 mg/100 mL), caffeic acid (11.1 mg/100 mL), caftaric acid (20.8 mg/100 mL), epicatechin (7.9 mg/100 mL), quercetin-3-O-glucoside (5.9 mg/100 mL), quercetin-3,4-O-diglucoside (4.2 mg/100 mL), quercetin-3-O-glucuronide (4.9 mg/100 mL), quercetin (30 mg/100 mL), isorhamnetin (12.6 mg/100 mL), piceid (2.2 mg/100 mL), resveratrol Gallic acid (8.9 mg/100 mL), caffeic acid (12.8 mg/100 mL), caftaric acid (25.1 mg/100 mL), epicatechin (12.6 mg/100 mL), quercetin-3-O-glucoside (7.8 mg/100 mL), quercetin-3,4-O-diglucoside (4.3 mg/100 mL), quercetin-3-O-glucuronide (3.8 mg/100 mL), quercetin (34.3 mg/100 mL), isorhamnetin (13.1 mg/100 mL), piceid (4.3 mg/100 mL), resveratrol (5.1 mg/100 mL), cyanidin-3,5-O-diglucoside (710 ng/100 mL), cyanidin-3-O -glucoside (106.9 ng/100 mL), cyanidin-3-O-acetyl-glucoside (40.8 ng/100 mL), peonidin-3,5-O-diglucoside (150.4 ng/100 mL), peonidin-3-O-glucoside (19.2 ng/100 mL), peonidin-3-O-acetyl glucoside (15.9 ng/100 mL), delphinidin-3-O-glucoside (877.4 ng/100 mL), delphinidin-3-O-acetyl-glucoside (210.3 ng/100 mL), delphinidin-3-O-p-coumaroyl-5-O-diglucoside (212.1 ng/100 mL), delphinidin-3-O-p-coumaroyl glucoside (211.7 ng/100 mL), petunidin-3-O-glucoside (210.1 ng/100 mL), petunidin-3-O-acetyl-glucoside (61.9 ng/100 mL), petunidin-3-O-p-coumaroyl-5-O-diglucoside (58.2 ng/100 mL), malvidin-3-O-glucoside (168.4 ng/100 mL), malvidin- Similar to studies on individual PPs, there are only a limited number of studies (9) evaluating the effect of extracts [30,32,33,36,[40][41][42] and of a phenolic-rich juice [31,43]. All of these studies were conducted in cell lines (six with Caco-2 cells and three with Caco-2/TC7 cells), and the experimental conditions differed considerably among the various studies.…”
Section: Effect Of Polyphenol-rich Products On Fru Uptake and Transpo...mentioning
confidence: 99%
“…The total PP concentration ranged from approximately 0.01 mg/mL [32,41] to 10 mg/mL [32], whereas the FRU concentration varied from 54 nM [41] to 130 mM [31]. Similarly, the method and duration of supplementation varied from co-supplementation with FRU for only 10 min [36] to pretreatment with phenolic extract for 24 h and subsequent incubation with FRU for 3 h [40]. Even though the use of different approaches makes it difficult to draw general conclusions, most studies reported a pronounced effect of most PP-rich products on both FRU uptake [32,36,[40][41][42] and transport [30,33,42,43].…”
Section: Effect Of Polyphenol-rich Products On Fru Uptake and Transpo...mentioning
confidence: 99%
See 1 more Smart Citation